KORELASI KADAR C-REACTIVE PROTEIN DENGAN JUMLAH TROMBOSIT PADA PENDERITA DIABETES MELITUS TIPE 2 - Nuswantoro, Ari; Wicaksono, Didik; Aditia, Aditia (Media Penelitian dan Pengembangan Kesehatan, 2023)
Type 2 diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia and insulin resistance, associated with decreased nitric oxide (NO) levels, increased free radical production, inflammation, endothelial dysfunction, and progressive vascular damage. C-reactive protein (CRP), an acute phase protein regulated by pro-inflammatory cytokines like interleukin-6 (IL-6), serves as a systemic inflammation marker. Pentameric CRP (pCRP) and monomeric CRP (mCRP) are implicated in mediating inflammation and endothelial dysfunction, with roles in endothelial cell adhesion, phagocytosis, inflammatory signaling, and interactions with endothelial cells, neutrophils, macrophages, and platelets. Additionally, leukocytes secrete platelet-activating factors, enhancing platelet activation and cytokine and chemokine release. This descriptive analytical study with a cross-sectional design aimed to investigate the correlation between CRP levels and platelet counts in patients with type 2 DM. Utilizing purposive sampling, 47 patients diagnosed with DM at Sultan Syarif Mohamad Alkadrie Hospital, Pontianak, during June 2023 were selected. CRP levels were measured using the fluorescence immunoassay (FIA) method, while platelet counts were determined through the impedance method. Statistical analysis employing Kendall's Tau-b test revealed a significant correlation (p < 0.05, r = -0.508), indicating that elevated CRP levels are significantly associated with reduced platelet counts in type 2 DM patients.